The potential role of exosomal miRNAs and membrane proteins in acute HIV-infected people - Li, Xin; Wang, Wenjing; Chen, Jing; Xie, Bangxiang; Luo, Shumin; Chen, Dexi; Cai, Chao; Li, Chuanyun; Li, Weihua (Frontiers in Immunology, 2022)
Exosomes have an important role during human immunodeficiency virus (HIV) acute infection. Yet, information regarding its cargo and its association with HIV rapid progressors (RPs) and typical progressors (TPs) remain largely unknown. In this study, exosomal miRNAs sequencing and mass cytometry were used to identify differential exosomal miRNAs and membrane proteins that participate in the pathogenesis of TPs and RPs. MiR-144-5p, miR-1180-3p, and miR-451a, miR-362-5p and miR-625-5p are associated with the TPs disease progression, and miR-362-5p with the RPs disease progression. Decreased autophagy, amino acid metabolism, immune response and IL-6 are closely related to the progression of RPs. SP1 was selected as the most significant transcription factor (TF) associated with disease progression. CD49D, CD5, CCR5, CD40, CD14, and CD86 were selected as the differential exosomal membrane proteins between TPs and RPs. This study provides valuable information for clarifying the mechanism in people with acute HIV infection, and it may eventually be of value for clinical practice.